The Role of Experiential and Viral Marketing Strategies in Increasing Brand Equity in Consumer Purchase Decisions for Tasikmalaya City Online Food Delivery Services - hana, Hana Diana Maria; Firdan Gusmara Kusumah (Jurnal Manajemen Bisnis, 2024)
This study uses a descriptive quantitative approach with data collection through questionnaires and interviews from 400 respondents. Data analysis was carried out with a combination of exploratory and confirmatory factor analysis (CFA) and model feasibility testing using SEM-AMOS with the Service-Dominant Logic (SDL) approach. The results of the study indicate that experiential marketing and viral marketing have a positive and significant influence on brand equity and consumer purchasing decisions. In addition, increasing brand equity also has a positive impact on purchasing decisions. This study provides a practical contribution to the development of marketing strategies in the online food delivery service industry by emphasizing the importance of integration and interaction in creating value for customers.